A new type of tomato puree with high content of bioactive compounds from 100% whole fruit. Issue 10 (3rd September 2020) - Romano, Raffaele; De Luca, Lucia; Manzo, Nadia; Pizzolongo, Fabiana; Aiello, Alessandra
Abstract : Abstract: In this work, a new type of tomato puree was obtained from the whole fruit including seeds and skins without any waste. Currently, the food industry aims to develop products that both bring benefits to consumer health and are ecosustainable. Several efforts in fact have been carried out to revalue tomato by‐products, such as seeds and skins, for human use. The physicochemical properties of the whole tomato puree immediately after production and after 6 months of storage were investigated and compared to the properties of a traditional tomato puree. Two tomato varieties were used in this study: Villa Literno and Piccadilly . pH, dry weight, water activity, titratable acidity, reducing sugars, soluble solid, lycopene, polyphenol, and volatile organic compound contents were evaluated. Tomato puree obtained from whole fruits mainly showed higher lycopene (90 to 150 mg/kg), flavonoid (39 to 41 mg/kg), and aldehyde (in particular hexanal) contents and a greater stability over time compared to those of the traditional puree. The proposed process allowed to obtain a tomato puree with a higher content of bioactive compounds, producing no waste. Practical Application: In this study, we proposed a new type of tomato puree made from the whole fruit. The whole tomato puree is richer in phenolic compounds and volatile organic compounds than the traditional puree that is made by removing skins and seeds. It can be an interesting product for the food industries because it is a source of bioactive compounds and reduces to zero the amount of waste.